Adaptive hysteresis and fuzzy logic controlled‐based shunt active power filter resistant to shoot‐through phenomenon. Issue 10 (1st October 2015) - Panda, Anup Kumar; Patel, Ranjeeta
Abstract : This study proposes a novel adaptive hysteresis and fuzzy logic controlled based 3‐phase 4‐wire full bridge interleaved buck active power filter (FB IB‐APF) which eliminates current harmonics without shoot‐through phenomenon. Besides mitigating current harmonics, special attention has been given to improve the reliability of the APF by eliminating shoot‐through current occurred in the converter circuit. The proposed APF topology consists of three single phase full bridge interleaved buck converter and therefore can be used for high voltage, medium‐to‐high power application. id – iq control strategy along with fuzzy logic controller (FLC) have been used for reference current generation. The results with PI controller have also been shown to prove the superiority of FLC. The adaptive hysteresis band current controller is being implemented to obtain optimised switching frequency. The performance of the proposed FB IB‐APF is evaluated under sinusoidal, unbalanced and non‐sinusoidal voltage source condition. Exhaustive simulation results are presented and finally verified with a real time digital simulator. The performance shows that FB IB‐APF brings the total harmonic distortion of the source current well below 5% adhering to IEEE‐519 standard. A comparison has also been made, based on switch device power between the IB‐APFs using for low power and high power application.